Digital Ethics and the Future of Education: An Urgent Dialogue - Augusto da Costa; Zelio da Conceicao Freitas (The Indonesian Institute of Science and Technology Research, 2025)
The rapid integration of digital technologies in educational environments has sparked critical debates on the ethical implications of such changes. While digital transformation offers unprecedented opportunities, it simultaneously raises concerns about privacy, equity, algorithmic bias, and the dehumanization of learning. This opinion article, grounded in current literature, explores the urgency of addressing digital ethics in education. It presents a conceptual framework that links ethical principles to digital educational practices and analyzes pressing ethical challenges. Through a structured discussion supported by data and literature, the paper highlights the necessity for a proactive and inclusive dialogue among stakeholders to ensure a morally responsible future for education.